THE EFFECTIVENESS OF INCENTIVES, WORK ENVIRONMENT AND LEADERSHIP STYLE ON THE PERFORMANCE OF TAPPERS IN AFDELING ZEELANDIA, ZEELANDIA PLANTATION, PTPN 1 REGIONAL 5 JEMBER - Adrinus Pinem (ABM: International Journal of Administration, Business and Management, 2025)
ABSTRACT In the scope of rubber plantations, the benchmark of tappers' performance can be seen from the acquisition of the Dry Rubber Content / Kadar Karet Kering (K3) value and the amount of dry rubber production produced. Referring to the data of K3 for the 2021-2023 periods, the cause of the low performance of tappers in Afdeling Zeelandia is suspected to be the habit of rubber tapping employees mixing latex with water and the incomplete tapping process. Based on this background, the researcher chose the variables of incentives, work environment and leadership style to measure their influence on performance. This study involved 95 samples of tapping employees by distributing questionnaires whose results were then analyzed using the SPSS version 25 application. It was found that partially incentives had no significant effect while the work environment and leadership style had a significant effect on the performance of tapping employees. Meanwhile, incentives, work environment and leadership style simultaneously have a significant effect on the performance of employees. The conclusions from the results above include that the low amount of incentives makes its influence cannot be felt by tappers, the work environment has the most dominant influence indicating that the cleanliness of rubber plantation land and maintenance of production roads that are routinely carried out are very needed and the finally a good relationship between leaders and employees is considered capable of improving employee performance. In this case the democratic leadership style needs to be developed further.